Sustainability in the Environmental Impact Assessment and Ecological Inputs for Quarry Activities in Melaka Tengah, Melaka - Rahimah Wahid (International Journal of Supply Chain Management, 2019)
In Malaysia the Environmental Impact Assessment (EIA) was introduced in 1988, as a measure of sustainability in developmental projects. The aim of this study was to examine the compliance with the guidelines and ecological adequacy of the information input in the preparation of the EIA report. The ecological input is an important part of the EIA. In this study, the choice was made for two EIA reports in Melaka which was sent to the DOE for approval. The method used was according to the revised package of measurement for 12 ecological input criteria in the EIA report. The results of this study found many omissions in the provision of ecological inputs and disobedience. Among the twelve criteria for assessment of the ecological inputs available in the description of the existing environment, consultants were not sensitive enough to identify the sample geology, flora and fauna and aquatic habitat. The review of the EIA report showed there were reports describing the effects of individual and yet try not to quantify these effects. For further description of mitigation measures to the physical aspect, no emphasis was made on the effectiveness of the proposed measures. In addition, mitigation measures were implemented. The residual impact was discussed briefly in both reports. The results of the survey in the vicinity of the project site also found a lot of environmental impact of specific ecosystems and flora and fauna of the river ecosystem. The dust pollution also affected the surrounding community. Overall, both the EIA report for the project was found to be less effective including information regarding ecological input and compliance aspects. A comprehensive and commitment of all parties is crucial to ensure continuity in the development process that can be achieved through improvements in the preparation of the EIA report mainly for information and compliance with ecological guidelines.